'We are nurses, they are doctors': Barriers to nurses' roles in pain management following surgery in Jordan. Issue 2 (13th October 2014) - Shoqirat, Noordeen
<x xml:space="preserve">Abstract</x> This study explored barriers to nurses' roles in pain management following surgery in Jordan. A qualitative approach using four focus group discussions (n = 4) was used. The total convenience sample of surgical wards nurses included 25 nurses. The analysis revealed two categories explaining the context and perceived barriers affecting nurses' roles in pain management. First were barriers within bedside nursing, comprising attention‐seeking patients, 'buzzer obsession' and family interferences. Second were barriers within nursing, comprising lack of staff and 'nurses need pain relief before patients', and the perception of 'we are nurses, they are doctors.' Nurses' roles in managing patients' pain following surgery is hindered by contextually complex barriers identified by this research. Multidisciplinary actions are therefore urgently needed to address barriers to pain management at the nursing professional, ward culture and policy levels. Failure to do so might lead to more pain sufferers following surgery, and thus poor recovery.